2018
DOI: 10.1007/s11695-017-2850-z
|View full text |Cite
|
Sign up to set email alerts
|

Food Tolerance and Eating Behavior After Roux-en-Y Gastric Bypass Surgery

Abstract: In the evaluation of mastication using almonds, food tolerance increased with the number of chewing cycles and with greater chewing efficiency; the same association was not found in the evaluation using red meat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
1
7
1
2
Order By: Relevance
“…A marked decrease in macronutrient intake is largely reported after bariatric procedures, so that food intake may result in a deficiency > 50 % in nutritional needs in some patients (19,20). In particular, protein consumption may fall dramatically and become insufficient, possibly due to intolerance of protein sources, mainly of meat (5,(21)(22)(23). Accordingly, our sample of patients submitted to RYGB exhibited a deficiency in protein intake (mean, 50 g/day), but this did not worsen in the long term, and they tolerated eating meat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A marked decrease in macronutrient intake is largely reported after bariatric procedures, so that food intake may result in a deficiency > 50 % in nutritional needs in some patients (19,20). In particular, protein consumption may fall dramatically and become insufficient, possibly due to intolerance of protein sources, mainly of meat (5,(21)(22)(23). Accordingly, our sample of patients submitted to RYGB exhibited a deficiency in protein intake (mean, 50 g/day), but this did not worsen in the long term, and they tolerated eating meat.…”
Section: Discussionmentioning
confidence: 99%
“…Patients frequently presented normal values for biochemical markers of protein and micronutrients at all study time points. The exception was lower levels of vitamin D in the preoperative period (17 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]) as compared to the reference value (30-100), which almost normalized during the postoperative period at 3 (26 [15-45]) and 12 months (26 [21][22][23][24][25][26][27][28][29][30][31][32]). Borderline hemoglobin and protein values were found in all of the study cutoff time points but remained within the normal range.…”
Section: Performance/monitoring Of Nutritional Supplementationmentioning
confidence: 99%
“…62 Considering that vitamin D deficiency is usually observed among people who cross with obesity and T2D, in addition to the fact that after mixed-type interventions only 28% of fats are absorbed and that a decrease of 5 to 10% of the Bone mineral density at 2 years after surgery, fat-soluble vitamins and bone metabolism should be closely monitored in these patients. 20,43,63,64 Most of the reduction in energy intake in these people responds to the reduction in the consumption of foods with added sugar and saturated fats. 52 Dumping Syndrome is associated with the selection of type, quantity, quality and consistency of ingestion of carbohydrates, it has been observed that the presence of symptoms leads these individuals to limit their selection, subsequently this deprivation promotes episodes of inappropriate choice and overfeeding, exacerbating them.…”
Section: Discussionmentioning
confidence: 99%
“…Los pacientes sometidos a CB poseen una menor capacidad gástrica, lo que limita el volumen, la variabilidad de ingesta; así como también existe una mayor posibilidad de presentar intolerancias alimentarias 14,15 . Lo anterior, sumado a la disminución del ácido clorhídrico, falta de factor intrínseco y disminución de la superficie de absorción intestinal, trae como consecuencia la deficiencia de micronutrientes 16 , que podrían generar importantes complicaciones si el paciente presenta mala adherencia a la suplementación indicada, falta de asistencia a los controles post-operatorios y exámenes programados.…”
Section: Micronutrientes En Cirugía Bariatricaunclassified
“…A pesar del conocimiento generalizado de las principales deficiencias de micronutrientes, la suplementación en la práctica clínica varía ampliamente. La tabla 2 muestra recomendaciones en la suplementación de vitaminas y minerales, y manifestaciones clínicas producto de la deficiencia 8,[16][17][18] .…”
Section: Micronutrientes En Cirugía Bariatricaunclassified